O percurso da lagarta: tradição e complexidade no ensino de língua inglesa em escolas de idiomas - Muriana, Marina Borges (2018)
In this research I investigate the phenomena traditional class, whose backbone is the coursebook, and complex class, based on the Complex Educational Design (CED), both from the students’ perspective. The phenomena emerge from experiences in English language classes for adults, at a language institute. The English proficiency level in Brazil is not satisfactory when compared to other countries and, associated to that, the contemporary world demands didactic alternatives which can be more inclusive, being able to embrace the interwoven network knowledge. Thus, I propose a reflection upon the contrasts between a traditional and a complex class, based on the essence arising from the description and interpretation processes of such classes. For this purpose, the methodological basis is the complex hermeneutic-phenomenological approach (FREIRE, 2010, 2012, 2017), which, for being a qualitative approach, enables the articulation of objectivity and subjectivity during the interpretation process, fostering the revelation of the essence of the human experiences’ phenomena studied. As theoretical support, I chose the complexity epistemology (MORIN, 1999, 2001, 2005, 2013, 2015) due to its articulation to the methodological approach used, which demonstrates its inter/transdisciplinarity from a teaching-learning point of view, according to Fazenda (2006, 2012) and Leffa (2006). To design the traditional classes, I used coursebooks by an international publisher and for its theoretical basis I found support in the studies of Paiva (2009), who brings a historical overview of the English language coursebook in Brazil, and Souza (1997-1998), who considers that a pedagogical weapon. To the complex classes, I chose a design based on the Complex Educational Design (FREIRE, 2013) proposing a course design based on complexity. Average forty-five-minute classes were taught to two different groups; each one had a traditional and a complex class and the teacher required the seven students to write a text describing the class they had just participated in. Fourteen texts were obtained, and they were interpreted based on the complex hermeneutic-phenomenological approach. From the texts describing the traditional classes, the following themes emerged: Grammar, Learning, Information, Transmission, Repetition and Dynamism. From the complex classes, the themes that emerged were Reflection, Discussion, Learning, Expression and Sharing. The contrasts between the themes of the two kinds of classes suggest that a complex design, for embracing traditional aspects, can be more inclusive, besides promoting reflections upon contemporary issues